2021
DOI: 10.3389/fphys.2021.710573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical Masks on Cardiopulmonary Function in Healthy Young Subjects: A Crossover Study

Abstract: Objective: Mask plays an important role in preventing infectious respiratory diseases. The influence of wearing masks in physical exercise on the human body needs to be studied. The purpose of this study is to explore the influence of wearing surgical masks on the cardiopulmonary function of healthy people during exercise.Methods: The physiological responses of 71 healthy subjects (35 men and 36 women, age 27.77 ± 7.76 years) to exercises with and without surgical masks (mask-on and mask-off) were analyzed. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 37 publications
4
48
2
1
Order By: Relevance
“…However, elevated blood carbon dioxide levels are an important cornerstone of the so called Mask-Induced Exhaustion Syndrome (MIES) (Table 2) [11]. A significant rise in carbon dioxide occurring while wearing a mask is scientifically proven in many studies [11,[18][19][20][21][22][23][24][25]27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], especially for N95-masks (Table 2) [20,[23][24][25]27,[30][31][32][33]35,[37][38][39]41,43,44], due to their higher deadspace and breathing resistance [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, elevated blood carbon dioxide levels are an important cornerstone of the so called Mask-Induced Exhaustion Syndrome (MIES) (Table 2) [11]. A significant rise in carbon dioxide occurring while wearing a mask is scientifically proven in many studies [11,[18][19][20][21][22][23][24][25]27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], especially for N95-masks (Table 2) [20,[23][24][25]27,[30][31][32][33]35,[37][38][39]41,43,44], due to their higher deadspace and breathing resistance [11].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent scoping review numerous important studies which provide statistically significant evidence for such CO 2 retention under the mouth-nose protection have been presented [11] and we have found additional studies that reveal scientific evidence of a carbon dioxide increase in the blood when masks are used. In total, significant changes (p<0.05) could be found in most of the evaluated studies that measured body CO 2 content during mask use [18,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] (Table 2). Experiments with relatively short evaluation times [45] or questionable study design [46,47] showed no effects caused by masks.…”
Section: Effects Of Masks On Carbon Dioxide Re-breathingmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of cycle ergometer exercise and progressive incremental exercise (ramp protocol) were used in the CPET protocol, which consists of 2 min of the resting stage, followed by 2 min of the unloaded pedaling stage (Unloaded stage: 0 watt/min), followed by 8–12 min of incremental/ramp exercise stage [Loaded stage: increased by ramp (watt/min), and the ramp was based on the formula as follow] until the subjects reach volitional exhaustion or the test is terminated by the medical monitor (see criteria for terminating the exercise test). This CPET study protocol was referred with our previous study [ 12 ]. Then, the participant ended with 3 min of recovery stage (0 watt/min) and 3 min of observation stage (static sitting).…”
Section: Methodsmentioning
confidence: 99%
“…The same was demonstrated in three other studies showing that during physical exertion, all masks are safe and have only minimal impact on performance and physiological variables [ 4 , 5 , 6 ]. However, during high-intensity exercise, wearing a face mask can have a relevant influence [ 7 ]. Children wearing FFP2/K95 masks were more stressed, which was shown, for example, by a higher breathing rate or higher end-tidal CO 2 .…”
Section: Introductionmentioning
confidence: 99%